Kepuasan Kerja Perawat pada Aplikasi Metode Tim Primer dalam Pelaksanaan Tindakan Asuhan Keperawatan (Studi Kuantitatif di Rumah Sakit Dr. Saiful Anwar Malang) - andriani, Lembah (Universitas Brawijaya, Indonesia, 2012)
Comprehensive nursing care that requires the professional nurse executive and nurse manager,one method that is able to provide nursing care to its full potential is the method of the primary team. Thisstudy was to determine whether there are differences in satisfaction before and after the interventionmethods of the primary team. To determine whether there is a primary method of application effect on jobsatisfaction of nurses satisfaction, the work itself, promotion, supervision, group work and working conditions.Respondents consisted of a nurse executive, who was given a closed questionnaire on nurse jobsatisfaction, then do the application of methods of primary team for 4 weeks, the conclusion of this study isthat working conditions affect job satisfaction, it is evident from the results of the study pre and postimplementation of the method the primary team, the indicator of working conditions scored an averagesatisfaction (9.5 to 11) with job satisfaction (64.3%), while the lowest satisfaction indicators contained inthe work itself (8.8 to 10) with a value of 57.1% job satisfaction.